The kiss of death : contagion, contamination, and folklore - Kitta, Andrea, 1977- (Utah State University Press, 2019)
"Disease is a social issue, not just a medical issue. Using specific legends and rumors, and exploring beliefs and practices that permeate notions of contagion and contamination, Kitta offers insight into vernacular conceptions of health and sickness and how medical and scientific institutions can use cultural literacy"--Provided by publisher